PENGARUH LAMA PEMANASAN PROSES FERMENTASI TERHADAP KADAR FENOLIK TOTAL DAN AKTIVITAS ANTIOKSIDAN BAWANG HITAM - Alfiatus Solichah; Nuniek Herdyastuti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
Black garlic is the result of the fermentation process at certain intervals so that is dark brown and has a fresh sweet taste. When compared to fresh garlic, black garlic does not have a strong off flavor due to the heating process which reduces the allicin content which is converted into the antioxidant compound S-allyl cysteine. The purpose of this study was to determine the effect of heating time fermentation process on total phenolic content and antioxidant activity of black garlic. Measurement of total phenolic content using the Folin-Ciocalteu method and using the DPPH method to measure its antioxidant activity. The experiment was conducted with different heating length treatment at intervals of 0 – 15 days. The results showed that the total phenolic content and antioxidant activity of black garlic increased with the length of heating time. The heating time had a significant effect (α = 0.05) on total phenolic content and antioxidant activity compared with garlic. Key words: black garlic, total phenolic content, antioxidant